Diagnosis of Salmonella enterica-induced septic arthritis in a healthy child using metagenomic next-generation sequencing: a case report - Ren, Min; Liao, Qiong (Frontiers in Pediatrics, 2025)
Salmonella enterica-induced arthritis frequently manifests in children with malignancies, sickle cell disease, immunodeficiency, or undergoing immunosuppressive therapy; however, its incidence in healthy children is rare. Here, we present a case of septic arthritis resulting from S. enterica infection in a previously healthy child, diagnosed utilizing metagenomic next-generation sequencing (mNGS). This case underscores the utility of mNGS in the clinical identification of S. enterica arthritis. Particularly in scenarios where the causative pathogen remains unidentified, mNGS emerges as a pivotal adjunctive diagnostic modality for uncommon pathogens.